2019
DOI: 10.1016/j.ejim.2018.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Multimorbidity in middle age predicts more subsequent hospital admissions than in older age: A nine-year retrospective cohort study of 121,188 discharged in-patients

Abstract: , E. K. (2019). Multimorbidity in middle age predicts more subsequent hospital admissions than in older age: A nine-year retrospective cohort study of 121,188 discharged in-patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 51 publications
(77 reference statements)
2
33
1
Order By: Relevance
“…3 44 Age was strongly associated with future hospitalisation and incident multimorbidity in our study and has been reported to increase hospitalised multimorbidity in elderly patients. 45 Many studies have found that women have a higher rate of multimorbidity than men, 6 44 46-48 but we observed the converse, with male sex strongly predicting future multimorbidity. The use of CCI in the context of prospective hospital admissions rather than cross-sectional multimorbidity in a primary care setting may explain the higher proportion of multimorbid men.…”
Section: Strengths and Limitations Of The Studycontrasting
confidence: 50%
“…3 44 Age was strongly associated with future hospitalisation and incident multimorbidity in our study and has been reported to increase hospitalised multimorbidity in elderly patients. 45 Many studies have found that women have a higher rate of multimorbidity than men, 6 44 46-48 but we observed the converse, with male sex strongly predicting future multimorbidity. The use of CCI in the context of prospective hospital admissions rather than cross-sectional multimorbidity in a primary care setting may explain the higher proportion of multimorbid men.…”
Section: Strengths and Limitations Of The Studycontrasting
confidence: 50%
“… 27 Most of the studies (n = 46, 60.5%) had a primary purpose of reporting the prevalence and patterns of multimorbidity. Of the total 76 studies, 52 (68.4%) were conducted in only six middle-income countries: Brazil, 27 42 China, 43 54 South Africa, 25 , 26 , 55 64 India, 65 72 Mexico 73 , 74 and Iran. 75 , 76 Studies based on multicountry data (n = 11) were based on data obtained from the World Health Organization’s (WHO’s) Study on Global Ageing and Adult Health (SAGE) and World Health Surveys.…”
Section: Resultsmentioning
confidence: 99%
“…[8][9][10] A retrospective cohort study in Hong Kong, which used hospital data to measure multimorbidity, found that middleaged patients with multimorbidity had a greater number of hospital admissions than older patients. 11 There is recognition of the need for greater understanding of the determinants and outcomes of multimorbidity in middle-aged adults. 11 12 Research in a variety of populations, using a range of multimorbidity definitions and measures, has found multimorbidity to be associated with increased mortality.…”
Section: Introductionmentioning
confidence: 99%